Mechanical circulatory support—Challenges, strategies, and preparations. Issue 5 (13th January 2021) - Awad, Wael I.; Bashir, Mohamad
Abstract: Background: Coronavirus disease 2019 (COVID‐19) is usually mild, but patients can present with pneumonia, acute respiratory distress syndrome (ARDS), and circulatory shock. Although the symptoms of the disease are predominantly respiratory, the involvement of the cardiovascular system is common. Patients with heart failure (HF) are particularly vulnerable when suffering from COVID‐19. Aim of the Review: To examine the challenges faced by healthcare organizations, and mechanical circulatory support management strategies available to patients with heart failure, during the COVID‐19 pandemic. Results: Extracorporeal membrane oxygenation (ECMO) can be lifesaving in patients with severe forms of ARDS, or refractory cardio‐circulatory compromise. The Impella RP can provide right ventricular circulatory support for patients who develop right side ventricular failure or decompensation caused by COVID‐19 complications, including pulmonary embolus. HT are reserved for only those patients with a high short‐term mortality. LVAD as a bridge to transplant may be a viable strategy to get at‐risk patients home quickly. Elective LVAD implantations have been reduced and only patients classified as INTERMACS profile 1 and 2 are being considered for LVAD implantation. Delayed recognition of LVAD‐related complications, misdiagnosis of COVID‐19, and impaired social and psychological well‐being for patients and families may ensue. Remote patient care with virtual or telephone contacts is becoming the norm. Conclusions: HF incidence, prevalence, and undertreatment will grow as a result of new COVID‐19‐related heart disease. ECMO should be reserved for highly selected cases of COVID‐19 with a reasonable probability of recovery. Special considerations are needed for patients with advanced HF, including those supported by durable LVADs.